An Analysis of Reading Materials in English Textbook for Class XI of Senior High School - Hulu, Deni Arnita; Sembiring, Elia Nova; Saragih, Erikson (LPPM Universitas Pancasakti Tegal, 2020)
This study aims to analyze the reading material in the English textbook of Class XI students, as well as to determine the types of reading texts available in the textbook and whether the type of reading text is under the 2013 Curriculum, and has met three aspects, namely the content aspect, the presentation aspect, and language use based on Pusat Perbukuan of the Ministry of National Education. Researchers used a qualitative research design where the results were be presented in words without statistical calculations. Another instrument was the checklist form used during the research analysis. The data were collected from reading materials in the textbook. The results showed that the reading materials in English textbooks were following the criteria for quality English textbooks recommended by Pusat Perbukuan of the Ministry of National Education.